Penyusunan Rencana Strategis Bidang Organisasi yang efektif Persit Kiznubika Pleton 2 - Senen; Gina Fauziah; Gatut Drajad (Universitas Pamulang, 2023)
The development of information and communications technology (ICT) has had a drastic impacton society and industry. Digital transformation generates new values and is a pillar ofindustrial policy in many countries around the world. In anticipation of this global trend, “″was introduced as the main or core concept in the 5th Basic Plan of Science and Technology,which was adopted by the Cabinet of Japan in January 2016. The Era of was identified as partof one of the growth strategies in Japan. We are now in a new era, where globalization and therapid evolution of digital technologies such as Artificial Intelligence (AI), Internet of Things(IoT) and robotics are bringing significant changes to citizens. Citizens' environments andvalues are becoming increasingly diverse and complex. Chart 1 below shows activity targetingnew digital technologies worldwide, which includes Industry 4.0, also known as “4th IndustrialRevolution”, Internet technology industry, and Made in China 2025.Keywords: Strategic, Planning, Organization